Proses Kognitif Siswa dalam Ekosistem Sekolah: Analisis Microsystem Bronfenbrenner dan Taksonomi Bloom - Ali Masdar Fahim; Intan Karisma; Abdul Kholiq; Abdurrahman Abdurrahman (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
School environment quality is widely believed to influence students' cognitive development, yet studies integrating Bronfenbrenner's microsystem framework with Bloom's Taxonomy remain scarce. This study examined the correlation between school environment quality, operationalized through physical classroom conditions, teacher–student relations, peer relations, and learning climate, and students' cognitive processes across six Bloom's Taxonomy levels. A quantitative correlational survey design was applied to 173 female students from an integrated Islamic institution spanning junior and senior high school, selected through proportionate stratified random sampling. A 48-item Likert-scale instrument was analyzed using Pearson correlation and multiple linear regression. Results showed a significant positive correlation between school environment and cognitive processes (r = .306, p < .001). The teacher–student relationship was correlated significantly with all six Bloom levels and was the only significant individual predictor in regression (Î² = .336, p = .001), with the model explaining 13.3% of variance. This study concludes that teacher–student relations emerged as the most consistently associated with microsystem component for students' cognitive processes across all Bloom's Taxonomy levels, showing stronger associations than physical conditions and classroom climate.